Scoping Review: Peranan Autoimunitas dalam Patogenesis COVID-19 - Namira Putri Hermawan; Maya Tejasari; Waya Nurruhyuliawati (Bandung Conference Series: Medical Science, 2022)
Abstract. COVID-19 is a disease that has become a new epidemic in the world today. COVID-19 is caused by a new Corona virus, namely severe acute respiratory syndrome coronavirus 2(SARS-CoV-2) or previously known as Novel Coronavirus 2019 (2019-nCov). The most common primary symptoms of COVID-19 are fever, dry cough, tachypnea, and shortness of breath. In cases of viral infection, there will be changes in the number of leukocytes, impaired liver enzyme function, and increased plasma inflammatory cytokines. People with COVID-19 who experience cytokine storm syndrome will cause an increased immune response so that it will lead to autoimmunity because there is a biomimicry of protein in SARS-CoV-2 as an antigen. This study aims to determine the role of autoimmunity in the pathogenesis of COVID-19. The type of research used is a scoping review. In this study, the sample consisted of 7 research articles that met the inclusion and exclusion criteria from the journal databases of Science Direct, Spingerlink, andPubMed. This study was conducted in the period March-December 2021. The results obtained in 7 articles stated that there was a relationship between the mechanism of autoimmunity and the pathogenesis of COVID-19. From 2 journals stated that there was a higher level of organ failure in COVID-19 patients who had autoimmunity. One article said that patients with COVID-19 with autoimmunity had lymphopenia in 85.7% of patients, eosinopenia in 66.7% of patients, thrombocytopenia in 23.8% of patients, high CRP in 94.7% of patients, and IL- 6 which was high in 89.5% of patients. Other journals say that the severity of COVID-19, mortality, and complications are high in COVID-19 patients with autoimmunity. Abstrak. COVID-19 merupakan suatu penyakit yang menjadi wabah baru di dunia saat ini. COVID-19 disebabkan oleh Corona virus baru yaitu severe acute respiratory syndrome coronavirus 2(SARS-CoV-2) atau yang sebelumnya dikenal dengan sebutan novel Coronavirus 2019 (2019-nCov). Gejala utama yang paling umum dari COVID-19 adalah demam, batuk kering, takipnea, dan sesak napas. Pada kasus infeksi oleh virus, akan ada perubahan jumlah leukosit, rusaknya fungsi enzim hati, dan meningkatnya sitokin inflamasi plasma. Orang dengan COVID-19 yang mengalami sindrom badai sitokin akan menyebabkan peningkatan respon imun sehingga akan mengarah ke autoimunitas karena ada biomimikri protein pada SARS-CoV-2 sebagai antigen. Penelitian ini bertujuan untuk mengetahui peran autoimunitas dalam patogenesis COVID-19. Jenis penelitian yang digunakan adalah scoping review. Dalam penelitian ini sampel terdiri dari 7 artikel penelitian yang telah memenuhi kriteria inklusi dan eksklusi dari database jurnal Science Direct, Spingerlink, danPubMed. Penelitian ini dilakukan pada periode Maret-Desember 2021. Hasil yang diperoleh dalam 7 artikel menyatakan bahwaditemukan hubungan mekanisme autoimunitas dengan patogenesis COVID-19. Dari 2 jurnal menyatakan bahwa terdapat kegagalan organ yang lebih tinggi pada pasien COVID-19 yang memiliki autoimunitas. Salah satu artikel mengatakan bahwa pasien pada COVID-19 dengan autoimunitas terjadi limfopenia pada 85,7% pasien, eosinopenia pada 66,7% pasien, trombositopenia pada 23,8% pasien, CRP yang tinggi pada 94,7% pasien, dan IL-6 yang tinggi pada 89,5% pasien. Jurnal lain mengakatan bahwa tingkat keparahan COVID-19, kematian, dan komplikasi tinggi pada pasien COVID-19 dengan autoimunitas.